Identifikasi Jamur Pada Pupuk Organik Cair (POC) Limbah Dapur Di Desa Sanur Kauh - HARVIANTO, ARDHIKA FAHRIZA; SUTARI, NI WAYAN SRI; ATMAJA, I WAYAN DANA (Agrotrop : Journal on Agriculture Science; Vol 12 No 1 (2022)DO - 10.24843/AJoAS.2022.v12.i01.p12, 2022)
Identification of Fungi in Kitchen Waste Liquid Organic Fertilizer (LOF) in Sanur Kauh Village . Decomposed kitchen waste contains certain microorganisms, one of which is fungus. Fungi are one of the microorganisms that are widespread in soil and water and have the potential in the process of decomposition of organic matter. The research objective was to determine the composition of kitchen waste and obtain fungi species from LOF of kitchen waste in Sanur Kauh Village. The research was conducted from September to December 2020. Sampling was conducted in Sanur Kauh Village, South Denpasar District. Furthermore, LOF making and analysis was carried out at the Laboratory of Soil and Environmental Sciences, Faculty of Agriculture, Udayana University and at the Indonesian Genetika Science Laboratory, Tangerang. The method used is a descriptive analysis experiment, which consists of field exploration, laboratory analysis and molecular identification. The results showed that the most dominant percentage of LOF from kitchen waste composition was fruit at 46.69% followed by vegetables at 24.17%, rice at 18.92%, egg shells, bones and meat at 5.16% and the remaining side dishes of 5.06%. The results of molecular identification of fungal species on LOF fermentation of kitchen waste isolates LDA 2 and LDB 2 were similar to Pichia kudriavzevii strain CBS5174 chromosome 2 (99.71%) and Pichia kudriavzevii culture CBS: 5147 (99.56%).